Type 1 cardiorenal syndrome in a patient with an acute infection caused by Trypanosoma cruzi in the Brazilian Amazon region - a case report - Petruccelli,Karla Cristina (2018)
Abstract Cardiorenal syndrome type 1 (CRS 1) occurs when acute heart failure leads to acute kidney injury. There are several etiologies of CRS 1, including Chagas disease. Here, we present the first case report of CRS 1 in a patient with acute Chagas disease. Electrocardiography, transthoracic echocardiography, and cardiac magnetic resonance imaging showed signs of acute myocarditis. Laboratory examination revealed severe loss of kidney function, with a creatinine clearance of 30 mL/min, which fully normalized after treatment. Due to emergence of Chagas disease in the Brazilian Amazon, it is important to report unique clinical features in order to improve patients’ outcomes.